Nanoparticle induced fusion of lipid membranes - Blasco, Sofía; Sukeník, Lukáš; Vácha, Robert (Nanoscale, 2024)
Membrane fusion is crucial for infection of enveloped viruses, cellular transport, and drug delivery via liposomes. Nanoparticles can serve as fusogenic agents facilitating such membrane fusion for direct transmembrane transport. However, the underlying mechanisms of nanoparticle-induced fusion and the ideal properties of such nanoparticles remain largely unknown. Here, we used molecular dynamics simulations to investigate the efficacy of spheroidal nanoparticles with different size, prolateness, and ligand interaction strengths to enhance fusion between vesicles. By systematically varying nanoparticle properties, we identified how each parameter affects the fusion process and determined the optimal parameter range that promotes fusion. These findings provide valuable insights for the design and optimization of fusogenic nanoparticles with potential biotechnological and biomedical applications.
Keywords: membránové lipidy; simulace molekulární dynamiky; Liposomes; Lipid Bilayers; Nanoparticles; lipidové dvojvrstvy; fúze membrán; Membrane Lipids; Molecular Dynamics Simulation; Membrane Fusion; liposomy; nanočástice